Patronal'nye izobraženija v programme rospisej Spasskoj cerkvi Evfrosin'eva monastyrja v Polocke - Sarab'janov Vladimir (Zograf, 2013)
The murals of Christ`s Transfiguration cathedral in Polotsk (ca. 1161), which were revealed during restoration in the last several years, include several thematic strata. Among them especially notable is a group of images, related to the patron saints. Distinguished among them are the figures of the patron saints of the Polotsk ducal family, to which St. Euphrosynia of Polotsk, the founder of the monastery and the builder of the Christ`s Church, belonged. The composition “Exaltation of the Cross” is set in one row with the patron saints, thus revealing semantic correlation with the ktitors` portrait in Kiev Saint Sophia and some other Kiev churches of tenth and eleventh centuries, where the idea of Russia becoming a member of Christian community is developed. At the same time, the patron theme is deeply intertwined with the purpose of the Christ`s Church to serve as a family burial for St. Euphrosynia.